2022
DOI: 10.3332/ecancer.2022.1470
|View full text |Cite
|
Sign up to set email alerts
|

Using the Khorana risk score to predict venous thromboembolism and overall survival in a cohort of Hispanic patients with solid malignancies

Abstract: Background:The Khorana risk score (KRS) for prognosis of venous thromboembolism (VTE) has been rarely explored in Hispanic populations.Objective: To determine the value of the KRS for prediction of VTE and overall survival (OS) among Hispanic individuals with cancer. Methods:We retrospectively evaluated all outpatients with newly diagnosed solid tumours receiving systemic chemotherapy in Hospital San Juan Dios, San José, Costa Rica, from January to December 2021. The 6-month cumulative VTE incidence according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Similarly, low specificity of Khorana model has also been reported in several studies. 21,22 Notably, despite satisfactory sensitivity at the calculated cutoff value, the Vienna CATS model classified over 50% of mCRC patients (> 700 patients) as high-risk, and its low positive predictive value (∼ 50%) indicated that a significant number of patients might be subjected to unnecessary risks associated with VTE prophylaxis. A similar trend was observed in the Protecht score with its calculated cutoff point.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, low specificity of Khorana model has also been reported in several studies. 21,22 Notably, despite satisfactory sensitivity at the calculated cutoff value, the Vienna CATS model classified over 50% of mCRC patients (> 700 patients) as high-risk, and its low positive predictive value (∼ 50%) indicated that a significant number of patients might be subjected to unnecessary risks associated with VTE prophylaxis. A similar trend was observed in the Protecht score with its calculated cutoff point.…”
Section: Discussionmentioning
confidence: 94%
“…Mulder et al's meta-analysis reported the Khorana score as a tool for selecting high-risk VTE in oncologic patients [33], and Akasaka-Kihara et al validated it in the Japanese cancer population [34]. Ramos-Esquivel et al recently found the Khorana score to perform an accurate categorization of VTE risk in ambulatory Hispanic patients who were newly diagnosed with solid tumors and were receiving systemic chemotherapy [35]. El-Sayed et al reported a calculated VTE occurrence probability of 87.5% when using the Khorana score at cut-off levels ≥ 3 in patients with hematological malignancy [36].…”
Section: Vte Risk Assessment Using Scoresmentioning
confidence: 99%